1970
DOI: 10.1111/j.1432-1033.1970.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Malate by Mitochondria Isolated from Cauliflower Buds

Abstract: 1. Pyruvate is the major product of malate oxidation by isolated cauliflower bud mitochondria when pyruvate dehydrogenase is inhibited. Pyruvate formation, which requires Mg++, Mn++ or Go++, is stimulated by added NAD.2. The effects of ADP, 2,4-dinitrophenol and respiratory inhibitors on pyruvate formation indicate that the reaction is linked to mitochondrial electron transport.3. No enzymic decarboxylation of oxaloacetate to pyruvate by the mitochondria can be observed. With added malate oxaloacetate breaks d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 28 publications
(26 reference statements)
0
36
0
Order By: Relevance
“…Other investigators claim that OAA is converted to pyruvate-not directly, but through malate dehydrogenase + NAD-malic enzyme activity (4,5,7,14). Data in this communication show that OAA added alone is not metabolized, indicating the absence of significant OAA decarboxylase activity in these mitochondrial preparations (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Other investigators claim that OAA is converted to pyruvate-not directly, but through malate dehydrogenase + NAD-malic enzyme activity (4,5,7,14). Data in this communication show that OAA added alone is not metabolized, indicating the absence of significant OAA decarboxylase activity in these mitochondrial preparations (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…It is also possible that the inhibition could have occurred as a consequence of the direct inhibition of the malic enzyme by oxaloacetate. Macrae [20] has reported that 2 mM oxaloacetate can act as a competitive inhibitor of the solubilised malic enzyme. The relationship between the inhibition caused by 0.2 mM oxaloacetate in the presence of increasing concentrations of malate, as the respiratory substrate, is shown as a LineweaverBurke reciprocal plot in Fig.4.…”
Section: Assay Of the Endogenous N A D F Poolmentioning
confidence: 99%
“…After preparation on self-generated Percoll gradients, avocado (Persea americana Mill, var be carried out by both MDH3 and ME (6,13,14,21), has recently been shown (25, 26) to exhibit a varying degree of cyanideinsensitivity, depending on the relative activity of either enzyme. It seemed promising, therefore, to re-examine malate oxidation by avocado mitochondria throughout the climacteric with special attention to the cyanide-insensitive alternative pathway.…”
Section: Introductionmentioning
confidence: 99%